2015
DOI: 10.18632/oncotarget.3622
|View full text |Cite
|
Sign up to set email alerts
|

Nimotuzumab increases the anti-tumor effect of photodynamic therapy in an oral tumor model

Abstract: Oral squamous cell carcinoma (OSCC) represents 90% of all oral cancers and is characterized with poor prognosis and low survival rate. Epidermal growth factor receptor (EGFR) is highly expressed in oral cancer and is a target for cancer therapy and prevention. In this present work, we evaluate the efficacy of photodynamic therapy (PDT) in combination with an EGFR inhibitor, nimotuzumab in oral cancer cell lines and OSCC xenograft tumor model. PDT is a promising and minimally invasive treatment modality that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…To address the limitations of therapeutic siRNA delivery, a new polymeric gene delivery system based on antibody h-R3 and PAMAM, is described that enhances intracellular delivery of siRNA. Nimotuzumab (h-R3) is a humanized monoclonal antibody (mAb) against human epidermal growth factor receptor (EGFR) that demonstrated a remarkable antiproliferative, pro-apoptotic and antiangiogenic effect [ 36 38 ]. Unlike other anti-EGFR monoclonal antibody, such as mAbs C225 and ABX-EGF, h-R3 did not provoke acneiform rash or folliculitis [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address the limitations of therapeutic siRNA delivery, a new polymeric gene delivery system based on antibody h-R3 and PAMAM, is described that enhances intracellular delivery of siRNA. Nimotuzumab (h-R3) is a humanized monoclonal antibody (mAb) against human epidermal growth factor receptor (EGFR) that demonstrated a remarkable antiproliferative, pro-apoptotic and antiangiogenic effect [ 36 38 ]. Unlike other anti-EGFR monoclonal antibody, such as mAbs C225 and ABX-EGF, h-R3 did not provoke acneiform rash or folliculitis [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some have found PDT to decrease the expression of EGFR in tumors in vivo or cells in vitro , while others have noted PDT-induced increases in both EGFR levels and its activation [ 14 , 21 , 34 , 35 , 36 ]. Bhuvaneswari et al [ 37 ] reported that hypericin-mediated PDT of xenografts of bladder tumors led to small increases in EGFR expression as measured by Western blotting, and more recently a similar finding was published for EGFR detection by immunohistochemistry after chlorin e6-mediated PDT of xenografts of oral squamous cell carcinoma [ 21 ]. Edmonds et al [ 34 ] reported PDT with benzoporphyrin derivative of multiple cancer cell lines to increase EGFR activation in the absence of changes in total EGFR levels.…”
Section: Resultsmentioning
confidence: 99%
“…This may in part be attributed to an activation of EGFR signaling in post-treatment proliferating disease when illumination was given at the higher rate of 150 mW/cm. EGFR is well established to contribute to resistance to cancer therapies and molecular targeting of the EGFR pathway can improve therapeutic outcomes to PDT and other types of treatment [ 20 , 21 , 37 , 41 ]. These data suggest that the addition of EGFR-targeting therapy may be particularly beneficial in combination with intrathoracic PDT when higher fluence rates are employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photodynamic therapy (PDT) is an approved new modality for the treatment of superficial solid tumor recurrent/refractory to conventional treatment based on photosensitizers exposed to light of specific wavelength [4, 5]. Among the photosensitizers, ZnO nanomaterials are regarded as the potential photosensitizing agents for PDT due to their unique phototoxic effect upon the irradiation [68].…”
Section: Introductionmentioning
confidence: 99%